JURIDICAL ANALYSIS OF REJECTION OF INKORTING BY TESTAMENTER HEIRS - Hermawan, Firza Ayudya; Rahandy Rizky Prananda (Awang Long Law Review, 2023)
The inheritance system that is enforced in Indonesia, among other things, is by using an inheritance system based on the Civil Code. This provision allows the deceased to bequeath his assets to ab intestato heirs or even to a third party by making a will or testament. Making a will allows the deceased to give some, a part, even all of their assets to other people, which opens the possibility of the absolute portion or Legitieme Portie being violated by the legitimatary heirs. In the event that the legal heirs object to the violation of the absolute portion, it is possible to reduce or inkorting the assets obtained by the testamentary heirs. This article aims to determine the position of a testament in an inheritance and whether or not a testamentary heir can rejected in the event of being decided to do inkorting using research using normative juridical methods. The conclusion obtained is that the position of the testament is considered higher because it is the final wish of the testator, but its application is still limited by Article 913 of the Civil Code. Meanwhile, incorruption cannot be rejected by the testamentary heirs, because the arrangements regarding the fulfillment of the legitieme portion are coercive. The conclusion obtained is that the position of the testament is considered higher because it is the final wish of the testator, but its application is still limited by Article 913 of the Civil Code. Meanwhile, incorruption cannot be rejected by the testamentary heirs, because the arrangements regarding the fulfillment of the legitieme portion are coercive. The conclusion obtained is that the position of the testament is considered higher because it is the final wish of the testator, but its application is still limited by Article 913 of the Civil Code. Meanwhile, incorruption cannot be rejected by the testamentary heirs, because the arrangements regarding the fulfillment of the legitieme portion are coercive.